Finance and Development, March 1972. (Finance and Development; Finance and Development, 1972)
This paper discusses the role of the IMF in financial stability and planning in world trade. The paper highlights that the IMF was set up to assist in the maintenance of an international monetary system that is conducive to the expansion of international trade. To this end, the IMF was provided with both a regulatory and financial role. In the execution of these functions, the IMF has gradually evolved as a center for international financial cooperation and a source of advice and technical assistance to its members.